Innovative Moments in Humanistic Therapy I: Process and Outcome of Eminent Psychotherapists Working with Bereaved Clients. Issue 3 (2nd July 2016) - Piazza-Bonin, Elizabeth; Neimeyer, Robert A.; Alves, Daniela; Smigelsky, Melissa; Crunk, Elizabeth
Abstract : This project entailed an intensive qualitative analysis of six-session psychotherapies conducted by three eminent humanistic psychotherapists working with bereaved clients. The Innovative Moments Coding System (IMCS), rooted in narrative therapy, is designed to measure change across therapy orientations. Research using the IMCS suggests that the psychotherapy change process occurs through the emergence, elaboration, and expansion of identifiable change moments for a client— innovative moments (IMs)—which present as exceptions to a client's presenting problematic narrative. There are five identified types of IMs: action, reflection, protest, reconceptualization (RC), and performing change (PC). The current study aimed to inform theory regarding the patterns of IMs across three humanistic approaches—constructivist, person-centered, and existential—when working with bereaved clients, while linking these patterns to observable change in each client's functioning. The alliance between each client and therapist was also assessed across the therapy process, showing consistently strong alliances across the three cases. Findings from the current study reinforce the salience of reflection, RC, and PC IMs in successful grief therapy cases, and also suggest the importance of meaning-making interventions in grief therapy. Clinical implications and suggestions for future research are also addressed.